1979
DOI: 10.1007/bf00848591
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and metamorphosis of the abdominal histoblasts ofDrosophila melanogaster

Abstract: The development of the adult abdomen ofDrosophila melanogaster was analyzed by histology, microcautery, and genetic strategies. Eight nests of diploid histoblasts were identified in the newly hatched larva among the polytene epidermal cells of each abdominal segment: pairs of anterior dorsal, posterior dorsal, and ventral histoblast nests and a pair of spiracular anlagen. The histoblasts do not divide during larval life but begin dividing rapidly 3 h after pupariation, doubling every 3.6 h. Initially they rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 32 publications
1
53
1
1
Order By: Relevance
“…Higher insects, i.e., those that undergo a complete metamorphosis, possess imaginal cells, a particular group of tissue-specific stem cell-like progenitors having unique characteristics, 30 and from which different adult structures originate during pupariation. The precursors of the adult abdomen epidermis are called abdominal histoblasts, 31 small cells specified during embryogenesis that show a characteristic pattern of cell cycle divisions: they arrest at the G 2 phase of mitosis but continue to grow in size throughout the larval instars until the onset of metamorphosis. At this stage they go through very rapid cell cycles and start to proliferate, showing the highest proliferation rate among all the imaginal cells during pupariation.…”
Section: A Role For Polo Alternative Polyadenylation In Metamorphosismentioning
confidence: 99%
See 1 more Smart Citation
“…Higher insects, i.e., those that undergo a complete metamorphosis, possess imaginal cells, a particular group of tissue-specific stem cell-like progenitors having unique characteristics, 30 and from which different adult structures originate during pupariation. The precursors of the adult abdomen epidermis are called abdominal histoblasts, 31 small cells specified during embryogenesis that show a characteristic pattern of cell cycle divisions: they arrest at the G 2 phase of mitosis but continue to grow in size throughout the larval instars until the onset of metamorphosis. At this stage they go through very rapid cell cycles and start to proliferate, showing the highest proliferation rate among all the imaginal cells during pupariation.…”
Section: A Role For Polo Alternative Polyadenylation In Metamorphosismentioning
confidence: 99%
“…At this stage they go through very rapid cell cycles and start to proliferate, showing the highest proliferation rate among all the imaginal cells during pupariation. [31][32][33] As a result, they expand and displace the surrounding larval epithelial cells (LECs) to form the abdominal epidermis. 32,34 When the abdominal histoblasts of the DpA2 transgenic individuals were analyzed by microscopy, we observed that they failed to proliferate at the pupa stage.…”
Section: A Role For Polo Alternative Polyadenylation In Metamorphosismentioning
confidence: 99%
“…Each anterior dorsal and ventral nest is composed of approximately 16 cells; each posterior dorsal nest consists of approximately five cells; and each spiracle nest has approximately three cells (Fig. 1A) (Guerra et al, 1973;Roseland and Schneiderman, 1979;Madhavan and Madhavan, 1980). During larval stages histoblasts are mitotically quiescent and arrested in G2 (Garcia-Bellido and Merriam, 1971;Madhavan and Schneiderman, 1977;Roseland and Schneiderman, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…1A) (Guerra et al, 1973;Roseland and Schneiderman, 1979;Madhavan and Madhavan, 1980). During larval stages histoblasts are mitotically quiescent and arrested in G2 (Garcia-Bellido and Merriam, 1971;Madhavan and Schneiderman, 1977;Roseland and Schneiderman, 1979). At the onset of metamorphosis histoblasts undertake a rapid proliferation that allows them to expand and fuse, at the expense of the preexisting surrounding polyploid larval epidermal cells (LECs) that commit programmed cell death (Madhavan and Madhavan, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The histoblasts divide and migrate dorsally and ventrally over the abdomen until its whole surface is covered with cells (Madhavan and Madhavan, 1980;Ninov et al, 2007;Roseland and Schneiderman, 1979). During this process, the LECs undergo apoptosis; they constrict apically, are extruded from the epithelium and are subsequently phagocytosed by hemocytes, which patrol underneath the epithelium (Ninov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%